Both AMP-activated and cAMP-dependent protein kinase regulate the expression of heat shock protein 70-2 gene in Neopyropia yezoensis - Zhenjie Sun; Zhenjie Sun; Wenhui Gu; Wenhui Gu; Wenhui Gu; Zezhong Feng; Yaqin Fan; Jianfeng Niu; Jianfeng Niu; Jianfeng Niu; Guangce Wang; Guangce Wang; et al. (Frontiers in Marine Science, 2022)
The upregulation of heat shock protein 70 (hsp70) gene under high temperature stress is a common phenomenon. Although heat shock protein-mediated stress responses play an important role in intertidal Neopyropia yezoensis, the detailed regulatory mechanism of the hsp70 gene expression is still unclear. Here, a full-length sequence of the hsp70-2 gene was cloned and its’ expression regulation was analyzed. There was an activating transcription factors element (ATFE) of cAMP-dependent protein kinase (PKA) was found at the gene promoter region and a highly conserved deduced amino acid sequence with calmodulin-binding activity was detected. Reagents implicated in the induction of the hsp70 gene were then selected to treat the algal samples at 24°C, and the photosynthetic parameters, transcription and translation of this gene were determined. Results showed that quercetin inhibited the transcription of the hsp70-2 gene, significantly decreased the synthesis of the HSP70-2 protein, and lowered the photosynthetic activity of N. yezoensis under high temperature stress conditions. Although the addition of trifluoperazine (TFP), an inhibitor of calmodulin (CAM), downregulated the photosynthetic parameters, the transcription of the hsp70-2 gene was not influenced at high temperature treatment, implying that CAM was not involved in the transcription of the hsp70-2 gene but involved in the heat stress reponding pathways. 5′-aminoimidasole-4-carboxamide-1-β-d-ribofuranoside (AICAR) promoted the synthesis of hsp70-2 transcripts significantly and HSP70-2 protein slightly, which indicated that AMPK regulated the induction of the hsp70-2 gene in N. yezoensis. Forskolin also promoted the upregulation of the hsp70-2 gene. Thus, both AMPK and cAMP-dependent protein kinase (PKA) could phosphorylate HSF and activate the expression of the hsp70-2 gene in N. yezoensis. However, there was no strict correlation between transcripts of the hsp70-2 gene and HSP70-2 protein contents. It was proposed that the posttranscriptional mechanisms were involved in regulating the synthesis of the HSP70-2 protein. Which allowed it to adapt to the extremely variable intertidal environments with an instant responding manner, since the accumulated transcripts could be translated rapidly when needed.